Accession of Spain & Portugal to the EEC : implications for the ACP states : final report (Interconsults KingstonJM, 1983)
Examines events since the Greek accession to the EEC and highlights lessons which ACP should derive form this experience. Discusses major issues of EEC foreign economic policy and draws conclusions about changes which Spain and Portugal might introduce. Analyzes EEC trade patterns indicating implications for ACP trade and production of accession of Spain and Portugal. Examines implications of enlargement for capital flows and migration and consequences for ACP. Briefly examines joint institutions established under the Lome convention with an indication of the likely impact of their functioning after enlargement. Discusses the legal implications of accession. Makes policy recommendations for the ACP.
IDS